Immunoinformatic and molecular docking approaches: siRNA prediction to silence cell surface binding protein of monkeypox virus - Rahatul Islam; Asif Shahriar; Muhammad Ramiz Uddin; Nour Fatema (Beni-Suef University Journal of Basic and Applied Sciences, 2024)
Abstract Background Monkeypox virus (MPV), an endemic pathogen in Africa, shares clinical similarities with smallpox. Recent reports indicate a concerning increase in the number of MPV cases detected outside its endemic region, highlighting the emergence of a multi-country outbreak. Given the importance of the cell surface-binding protein E8L in facilitating viral attachment to host cells, this study aimed to identify potential small interfering RNAs (siRNAs) capable of silencing E8L and thereby serving as a basis for therapeutic development. Results siRNAs have emerged as promising candidates for genetic therapies and antiviral and antibacterial treatments. In this investigation, we employed computational assays, including GC content analysis, binding free energy assessment, folding properties evaluation, melting temperature determination, and siRNA efficacy prediction. Our comprehensive analysis identified five siRNAs with high potential for effectively silencing the cell surface-binding protein of the monkeypox virus. Among these siRNAs, molecular docking revealed that “S8” (Guide-UUAUGGAUCCAAUCACUUGAU, Passenger-CAAGUGAUUGGAUCCAUAAUC) demonstrated the strongest affinity with the human argonaute-2 protein. Conclusions The siRNA “S8” represents a promising therapeutic target for developing treatments against monkeypox virus infection by specifically silencing the cell surface-binding protein E8L. Our research lays the foundation for future endeavors in genome-level therapies. It can potentially create chemically produced RNA molecules as effective antiviral drugs targeting Monkeypox virus infection. These findings contribute to advancing therapeutic strategies and offer new avenues for combating the spread of MPV, particularly in regions affected by the multi-country outbreak.